Outdoor recreation in ecosystem service accounting: pilot accounts from Finland. Issue 3 (18th May 2020) - Lankia, Tuija; Neuvonen, Marjo; Pouta, Eija; Sievänen, Tuija; Torvelainen, Jukka
ABSTRACT: Ecosystem accounting is a coherent framework for integrating measures of ecosystems and the flow of services they provide to the national accounting of economic activity. Here we focus on the accounting of cultural ecosystem services, particularly, nature-based recreation in open access conditions in Finland. The aim is to improve national capacity to proceed to ecosystem accounting by illustrating possibilities in existing data and knowledge and by identifying data gaps. We apply the United Nations System of Integrated Environmental Accounting – Experimental Ecosystem Accounts (SEEA EEA) framework for recreation accounting to test its applicability, and to show how existing national forest and outdoor recreation-related data sets can support accounting. Assessment of the extent of recreational resources is based on data from areas available for recreation. In the assessment of recreational use, we illustrate how nationwide survey data can provide an estimate of the number of recreational visits to nature areas and a solid base for monetary accounts. We identify gaps in the extent, supply and use data for recreational ecosystem services.